2012
DOI: 10.5604/15093492.992297
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of diagnoses in patients with spinal cord injury referred to hospital rehabilitation departments

Abstract: Risk factors for IDRD in SINC patients include complete neurological deficit, short time elapsing from SINC, referral from a hospital, referral from a surgical department, thoracic spinal lesion, and multiple co-morbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The condition has a male preponderance. This is a mesodermal disorder with defect in reparative process [2,3] causing heterotopic ossification which usually begin in 5-7 years of life [4]. Our case however, has history of ossifications from first year of life.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The condition has a male preponderance. This is a mesodermal disorder with defect in reparative process [2,3] causing heterotopic ossification which usually begin in 5-7 years of life [4]. Our case however, has history of ossifications from first year of life.…”
Section: Discussionmentioning
confidence: 68%
“…This is sometimes associated with stiffness and decreased mobility at joint site resulting in progressive contractures [2]. This case also had this characteristic pattern.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Previous studies have already shown inconsistent results in terms of interrater reliability and test-retest reli ability of MAS in SCI, limiting its validity. 25,41,[50][51][52][53] Although the measurements were taken in a standardized manner by the same clinician, different factors already reported in previous studies hindered the assessment of spasticity in the iSCI population, such as the difficulty to distinguish spasticity from passive viscoelastic changes, the presence of clonus, and ROM limitation. 50 Despite the fact that the MAS is the most widely used tool to assess the effectiveness of rehabilitation interventions for the treat ment and management of spasticity in the SCI population, 54 other tools like the Spinal Cord Assessment Tool for Spastic reflexes, 55 which has been shown to be a valid measure of 3 different types of spastic motor behaviors in SCI, could be considered an alternative to the MAS for assessing the con struct validity of the SCIGDI.…”
Section: Discussionmentioning
confidence: 99%
“…These diagnostic skeletal manifestations include ectopic calcifications, short hallux with either monophalangism or synphalangism, bilateral halluces valgus (75-90%), short 1st thumbs secondary to short first metacarpals, restricted range of motion of shoulders, kyphoscoliosis with lumps over the back, intellectual disability, alopecia and cardiac conduction defect are other rare finding. 10,11 It is important to remember that these features may not always accompany the condition, and besides, there are many genetic conditions in differential diagnosis with overlapping skeletal features.…”
Section: Discussionmentioning
confidence: 99%